GAMBARAN KEJADIAN KANKER PROSTAT PADA PENDERITA DIABETES MELLITUS DI RSUP H. ADAM MALIK MEDAN - Surya Martua Horas Harahap (Fakultas Keperawatan Institut Kesehatan Deli Husada, 2018)
According to Kemenkes RI, in 2013, the number of prostate cancer patient is 0.2% or approximately 25,012 patients. Prostate cancer is a malignancy in the prostatic gland and more than 95% of prostate cancer is adenocarcinoma, the other 5% is transitional cell and neuroendocrine carcinoma or sarcoma. Up to now, the etiology of prostate cancer is still unknown, but it involves multifactor and genetic mutations. This study is a descriptive study design with a retrospective cross sectional in the Urology Division of the Department of Surgery, General Hospital of H. Adam Malik Medan during period January to December 2014. From this study we found about 261 patients of Diabetes Mellitus who visited surgery, but only as many as 41 people (15.7%) performed prostate biopsy, and of the 41 people who had the most prostate cancer were 24 people (58.5%). The highest age range was 70-74 years (37.5%), with PSA values more than 50 ng / ml as much (33.3%), and the highest Gleason score in the range of 5-6 (50%)